Discourse of national clothes in kazakh and turkish proverbs (Journal of Oriental Studies, 2024)
National clothing is not only the main indicator of the adaptation of each ethnic group to the environment, it also provides information about its lifestyle, tastes, ethics, and aesthetics. The clothes used in the composition of proverbs, as part of culture, reveal in the context the essence of linguistic and figurative thinking, which determines the cultural nature of the nation and forms the mentality of the people. As a component of proverbs, the names of the national clothing are an example of the interweaving of cultural images and linguistic images of the world in the context of concepts with their symbolic content and the discourse that arises on its basis.This article discusses the discourse of the names of national clothes in the proverbs of the Kazakh and Turkish ethnic groups, belonging to the Turkic-speaking peoples, in a cultural and contextual context. Based on the interpretation of proverbs, their scope and functions are analyzed. When the names of the clothing that found in Kazakh proverbs are considered separately it characterizes such clothing as “borik”, “zhaulyk”, “ton”, “shapan”, “kebenek”, “takiya”, which determine the national character. In the process of comparing Kazakh and Turkish proverbs, it was found that in proverbs and sayings common to the two nations, the names of clothes “borik” and “ton”, dating back to Turkic times, were preserved in the form of a cultural code. However, it is clear that such clothes as “fes”, “kurk”, “aba”, “elbise” and their names, reflecting the national characteristics of the Turkish people and started to formalize as a  cultural code. The emergence of the process of replacing Turkic cultural codes, such as "borik", "ton", with those borrowed from the Arabic language, was marked by two main factors: the process of adaptation to the environment and the linguistic and cultural integration of neighboring countries.The disclosure of the discourse associated with the names of clothes in Kazakh and Turkish proverbs helps to identify the directions, content of linguistic and mental transformation, determines the relevance of the work.Key words: names of national clothes, Kazakh proverb, Turkish proverb, discourse, interpretation, cultural constant.